2002
DOI: 10.1021/jm0209578
|View full text |Cite
|
Sign up to set email alerts
|

Homology Modeling of Rat and Human Cytochrome P450 2D (CYP2D) Isoforms and Computational Rationalization of Experimental Ligand-Binding Specificities

Abstract: The ligand-binding characteristics of rat and human CYP2D isoforms, i.e., rat CYP2D1-4 and human CYP2D6, were investigated by measuring IC(50) values of 11 known CYP2D6 ligands using 7-methoxy-4-(aminomethyl)coumarin (MAMC) as substrate. Like CYP2D6, all rat CYP2D isozymes catalyzed the O-demethylation of MAMC with K(m) and V(max) values ranging between 78 and 145 microM and 0.048 and 1.122 min(-1), respectively. To rationalize observed differences in the experimentally determined IC(50) values, homology model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 39 publications
1
85
0
1
Order By: Relevance
“…We have used the latter molecular approach, combining experimental analysis of substrate binding with protein modeling, to study CYP2D6 active site-ligand interactions. This has helped us (Kirton et al, 2002;Paine et al, 2003;Flanagan et al, 2004;Kemp et al, 2004;McLaughlin et al, 2005) and others (Venhorst et al, 2003;Keizers et al, 2004Keizers et al, , 2005 to identify residues that play a key role in metabolism, and to determine the binding orientation and affinity of ligands in the active site (Kirton et al, 2002;Kemp et al, 2004). The recently determined crystal structure of CYP2D6 (Rowland et al, 2006) has confirmed the correctness of many of the features of the active site of our model of the enzyme.…”
supporting
confidence: 58%
“…We have used the latter molecular approach, combining experimental analysis of substrate binding with protein modeling, to study CYP2D6 active site-ligand interactions. This has helped us (Kirton et al, 2002;Paine et al, 2003;Flanagan et al, 2004;Kemp et al, 2004;McLaughlin et al, 2005) and others (Venhorst et al, 2003;Keizers et al, 2004Keizers et al, , 2005 to identify residues that play a key role in metabolism, and to determine the binding orientation and affinity of ligands in the active site (Kirton et al, 2002;Kemp et al, 2004). The recently determined crystal structure of CYP2D6 (Rowland et al, 2006) has confirmed the correctness of many of the features of the active site of our model of the enzyme.…”
supporting
confidence: 58%
“…1, IC 50 = 0.6 nM) was positioned into the extended binding cleft of renin (S3 to S2' subsites) making interactions with the hydrophobic cavity, which has not been previously explored. It is interestingly to note that pharmacokinetic properties and drug metabolism can also be examined and improved by exploring crystal structures of the human cytochrome P450 isoforms [17,18].…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…1, IC 50 = 0.6 nM) was positioned into the extended binding cleft of renin (S3 to S2' subsites) making interactions with the hydrophobic cavity, which has not been previously explored. It is interestingly to note that pharmacokinetic properties and drug metabolism can also be examined and improved by exploring crystal structures of the human cytochrome P450 isoforms [17,18].The receptor-based approach is carried out in an iterative manner, proceeding via multiple computational and experimental paths until the development of an optimized lead compound having high affinity and selectivity, as well as optimized pharmacokinetic properties, as shown in Fig. (2).…”
mentioning
confidence: 99%
“…Other possibilities for modeling studies include the move toward methods that do not require detailed ligand alignments (Balakin et al, 2004) and incorporate more information derived from determined protein structures and/or homology models. Improved homology models are also leading to more progress in molecular dynamics approaches in describing human P450 isoforms whose structure has not yet been determined (e.g., 2D6) (Venhorst et al, 2003;Kemp et al, 2004). One intriguing approach even uses 3D-QSAR to refine homology models before they are used for further docking to improve the ligand alignments (Evers et al, 2003).…”
Section: New Uses Of 3d-qsarmentioning
confidence: 99%